PELAKSANAAN PERJANJIAN KERJA SAMA ANTARA PEMERINTAH KOTA SAMARINDA DENGAN PT PARWITA KARYA TENTANG PEMBANGUNAN DAN PENGELOLAAN TERMINAL ANTAR PROVINSI SUNGAI KLEDANG DI SAMARINDA - Endra Ari Wijayanto (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTIONEndra Aris Wijayanto, Fakultas hukum, University 17 August 1945, Samarinda Kalimantan East. Execution Of Cooperation Agreement Between Government Of Town of Samarinda With PT. Prawita Masterpiece About Development And Management Of Terminal Passenger Of River of Kunjang In Samarinda Defect. [In] guiding by DrawanHasyim, SH, M.Si and of Dr. H. Abdul Rokhim, SH, M.Hum.Target of this research [is] academic study to execution of agreement of development and management of bus terminal of type A [in] Samarinda defect with PT Perwita masterpiece with and oprete build system of[is transfer of   ( BOT) require to be [done/conducted] as discourse effort and socialization to wide of society.Result of this research study and solve problem like : A. Form is same work agreement between government of town of Samarinda with [party/ side] of parwita masterpiece about development and management of terminal passenger of A type [in] river of kledangsamarinda defect B. Execution of is same work agreement between pemerintah with PT Parwita masterpiece about development and management of terminal of type A [in] river of kledang Samarinda defect.Pursuant to result of research that side which is one principal, assigning to developer ( kontraktor) to work contract with payment of fee or price. Contract agreement arranged in Section 1604 to 1616 KUHPERDATA and special regulations which made by government like Keppres No.16 year 1994, A.V.1941 and others